Clinical outcome of the artificial iris diaphragm in silicone oil surgery. Issue 7 (9th March 2012) - Hermann, Manuel M; Muether, Philipp S; Kuhn, Leonie; Kirchhof, Bernd; Fauser, Sascha
Abstract : Background: Some eyes require long-term silicone oil tamponade. Problems arise in aphakic eyes with iris defects or hypotony, because an inferior iridectomy can not prevent silicone oil from entering the anterior chamber causing keratopathy and glaucoma. The artificial iris diaphragm was developed to prevent these complications. Methods: In this retrospective case series, 94 consecutive aphakic eyes of 94 patients received an artificial iris diaphragm and a silicone oil tamponade. All eyes had hypotony or iris defects. The primary outcome measure was the retention of silicone oil behind the iris diaphragm. Secondary outcome measures included visual acuity, intraocular pressure and surgical revisions. Results: The mean follow-up time was 586 days. No silicone oil in the anterior chamber at the last follow-up visit was found in 58 cases (61.7%). The Kaplan–Meier survival analysis returned a mean survival time for a functional diaphragm of 1227 days. Keratopathy improved in 55.3% at least temporarily, and vision improved or remained stable in 38.2% until last follow-up. The diaphragm was more successful when the underlying disease was trauma or congenital malformation. Conclusions: The artificial iris diaphragm often retained silicone oil from the anterior chamber in severely damaged eyes. It can be useful to prevent phthisis and preserve vision.